Influence of blood groups on maximum oxygen consumption and explosive power among high-level basketball players in Palestine - Qadumi, Abdelnaser; Yousef, Iyad; Qadoume, Ali (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
The study aimed to identify the influence of blood groups on maximum oxygen consumption (VO2max) and explosive power in high-level basketball players in Palestine. The researchers used a descriptive-analytical approach. The study was conducted on a healthy random sample of 44 players, whose age, height, and body mass were 25.81 ± 5.79 years, 187.79 ± 9.52 cm, and 89.97 ± 15.61 kg, respectively. The players were tested using the vertical jump test and the Cooper 12-minute run test. The results of the study revealed that the mean explosive power was 47.27 cm, and the mean maximum oxygen consumption (VO2max) was 42.04 mL/kg/min. In addition, blood group had a statistically significant effect on both maximum oxygen consumption and explosive power, with blood type B showing higher explosive power and blood type O showing higher VO2max (p < 0.05). Blood group appears to influence physiological performance in high-level basketball players, with blood type O associated with higher aerobic capacity (VO2max) and blood type B associated with greater explosive power. These findings suggest that blood type may be a factor to consider in athlete assessment and training.